Telaah Basis Filosofis Ekowisata: Dari Ontologi, Epistemologi Hingga Aksiologi - Aji, Khusnul Bayu (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2023)
Many studies have been conducted to investigate the philosophical issues of ecotourism, but none has explicitly addressed the components of ecotourism's ontology, epistemology, and axiology. Therefore, the purpose of this article is to examine the philosophical foundations of ecotourism from the perspectives of ontology, epistemology, and axiology. A literature review was employed in this article. According to analysis, the ontological basis of ecotourism, which emerged in the mid-1980s as a manifestation of alternative tourism and as a ‘face’ of sustainable tourism, is intimately linked to 'nature,' which is constituted by the generative power of a transcendent principle of unity, being, and goodness. In this sense, ecotourism philosophy centers on the notion that unique sites for ecotourism purposes are considered 'paradises'. Tourists and inhabitants of these unique places should engage in ecotourism with consciousness; that is, the place should be conserved intact, as originally discovered. The epistemology of ecotourism is constructed as an abstraction of a relationship that cannot be separated between humans and the environment in the context of tourism. From an axiological standpoint, ecotourism is based on environmental values and ethics that should be included in the tourism industry to foster harmony between humans and nature as a good existence.